P2Y2 receptor deficiency aggravates chronic kidney disease progression - Potthoff, Sebastian A.; Stegbauer, Johannes; Becker, Jan; Wagenhaeuser, P. J.; Duvnjak, Blanka; Rump, Lars C.; Vonend, Oliver (Frontiers in Physiology, 2013)
Purinergic signaling is involved in a variety of physiological states. P2 receptors are mainly activated by adenosine triphosphate (ATP). Activation of specific P2Y receptor subtypes might influence progression of kidney disease. To investigate the in vivo effect of a particular P2 receptor subtype on chronic kidney disease progression, subtotal nephrectomy was performed on wild type (WT) and P2Y2 receptor knockout (KO) mice. During the observational period of 56 ± 2 days, survival of KO mice was inferior compared to WT mice after SNX. Subtotal nephrectomy reduced creatinine clearance in both groups of mice, but the decrease was significantly more pronounced in KO compared to WT mice (53.9±7.7 vs. 84.3±8.7µl/min at day 56). The KO mice also sustained a greater increase in systolic blood pressure after SNX compared to WT mice (177±2 vs. 156±7 mmHg) and a 2.5-fold increase in albuminuria compared to WT. In addition, WT kidneys showed a significant increase in remnant kidney mass 56 days after SNX, but significant attenuation of hypertrophy in KO mice was observed. In line with the observed hypertrophy in WT SNX mice, a significant dose-dependent increase in DNA synthesis, a marker of proliferation, was present in cultured WT glomerular epithelial cells upon ATP stimulation. Markers for tissue damage (TGF-β1, PAI-1) and proinflammatory target genes (MCP1) were significantly upregulated in KO mice after SNX compared to WT SNX mice. In summary, deletion of the P2Y2 receptor leads to greater renal injury after SNX compared to WT mice. Higher systolic blood pressure and inability of compensatory hypertrophy in KO mice are likely causes for the accelerated progression of chronic kidney disease.